Dribble like Robben: what determines successfulness in 1-vs-1 actions in elite soccer? - Oonk, G. A.; Kempe, M.; Buurke, T. J. W.; Lemmink, K. A. P. M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Competitive interactions are an important phenomenon in most team and individual sports. However, research on competitive interactions is mainly conducted in controlled laboratory-based experiments, which raises the question of generalizability towards more dynamic environments in team sports. While studies in rugby and futsal investigated 1-vs-1 actions in training settings, they did not relate their findings to the successfulness of the actions. We seek to close this gap by studying 1-vs-1 actions in competition. Therefore, using a large-scale observation design, this study aims to identify determinants of successful 1-vs-1 actions in male elite soccer. METHODS: 1-vs-1 actions from 43 Dutch Eredivisie matches were manually selected and labelled on successfulness by three raters. Using tracking data, 24 variables of the 1-vs-1 actions were obtained, divided into three categories: individual (e.g. velocity of the defender), interaction (e.g. relative velocity between the attacker and the defender), and environmental (e.g. the location on the pitch of the action). Multivariate analysis was used to show which (category of) variables discriminated between successful and unsuccessful 1-vs-1 actions. RESULTS: In total 734 1-vs-1 actions were selected (Fleiss kappa = 0.76) of which 356 were successful and 378 unsuccessful (Fleiss kappa = 0.89). A MANOVA showed a main effect for successfulness (Wilks * = 0.881, F(23, 710) = 4.178, p < 0.001). Post-hoc analysis with a Bonferroni correction identified five individual variables that differed between successful and unsuccessful 1-vs-1 actions (p